Regional aspects of associations of the CYP2C19 gene polymorphism with coronary atherosclerosis in acute coronary syndrome - K. Yu. Nikolaev; I. A. Urvantseva; K. Yu. Batueva; K. A. Apartsin; A. V. Gorokhova; V. I. Ganyukov; N. A. Kochergin; E. M. Zelenskaya; G. I. Lifshitz (Российский кардиологический журнал, 2018)
Aim. To study the associations of allelic variants of the CYP2C19 gene with atherosclerotic lesions of the coronary arteries in patients with acute coronary syndrome (ACS) in the North of Siberia (Surgut) and in large cities of the Siberian Federal Okrug (SFO).Material and methods. During the study 296 patients with ACS were examined at admission to cardiology hospitals in large cities of the North (Surgut, 114 patients) and SFO (Irkutsk and Kemerovo, 182 patients). All patients underwent coronary angiography and genetic research (identification of CYP2C19*2, CYP2C19*3 and CYP2C19*17 alleles).Results. In patients with ACS living in the North of Russia allelic variant CYP2C19*17 (*17/*17) is positively associated with the severity of lesion of left coronary artery (LCA) (χ2=9,81; p=0,002), as well as with at least 50% stenosis, more than 70% lesion of the proximal or middle part of the three main arteries, or more than 50% lesion of LCA trunk (χ2 =6,52; p=0,011), and previous myocardial infarction (χ2=8,15; p=0,004). Among patients with ACS living in cities of the Siberian Federal Okrug, the allelic variant CYP2C19*17 (*17/*17) is directly associated with diabetes mellitus (χ2=5,48; p=0,019) and less than 45% left ventricular ejection fraction (χ2=4,20; p=0,040). Regression analysis showed that in patients with ACS living in the northern region of Russia, only the allelic variant CYP2C19*17 (*17/*17) correlated with at least 50% stenosis of LCA trunk (Exp (B): 11,623, 95% CI: 1,893; 71,342; p=0,008). It did not correlate with the male sex, age, smoking and diabetes (p>0,05).Conclusion. The results show the presence of direct associations of CYP2C19*17 alleles with prognostically unfavorable coronary atherosclerosis in ACS patients living in the North of Siberia.